"It ain't 'nah' it's 'no'": Preparing preschoolers for the language of school. (December 2018) - Whittingham, Colleen E; Hoffman, Emily Brown; Rumenapp, Joseph C
This research presents reflections from focus group discussions with childcare providers and parents of preschoolers in one African American community situated within a large Midwestern city in the United States. The purpose of this study was to examine parents' and childcare providers' conceptions of literacy and language related to school readiness. During these conversations it became clear that both parents and providers engage in a number of practices to prepare children to use the standard variety of English privileged by mainstream schooling. Participants verbalize the dual importance of encouraging all language development for young children while explicitly teaching the uses of language as situated in a larger social context. Both parents and providers discuss the need to build a bridge for children between the English varieties used at home and the standard English valued by schools. In light of these findings, the authors problematize common conceptions of 'school readiness' as unidirectional and discuss implications for children entering school settings where language varieties are undervalued.